Eficiencia organizacional a través de la implementación de prácticas de gestión de cambio en la alta dirección del Gobierno Provincial de Los Ríos - Cabezas Astudillo, María Bertili (2023)
Organizational efficiency is a term that denotes the ability of an organization to achieve its objectives, where it uses the least amount of resources possible. On the other hand, it is usually known as an indicator of how a company or organization can convert its inputs into products and/or services, in other words, it aims to do a little more with fewer resources. Change management practices are recognized as the process with which changes in an organization are prepared and managed during said process; Everything relevant and pertinent is prepared for the transition to the new change, it is there where the support of the company is obtained and it is implemented in a timely manner. The most important thing in change management practices is to address these changes consciously and from different perspectives. In the Provincial Government of Los Ríos, the productivity of public servants is directly related to the results and business performance of each person; That is why, due to low performance in the overload of activities carried out in the different departments, the performance of its employees decreases, this causes that; These employees present complaints to senior management and in turn they are not resolved. The results of the research indicate that the officials who work in all their work units do not implement change management practices to increase organizational efficiency, which leads to problems in the administration, due to low motivational performance. that has said personnel.